Fuzzy PI controlled inverter for grid interactive renewable energy systems. Issue 7 (1st September 2015) - Sefa, I.; Altin, N.; Ozdemir, S.; Kaplan, O.
Abstract : In this study, a fuzzy‐PI controlled grid interactive inverter has been designed and implemented. The proportional and integral gains of the PI controller are decided and tuned by the fuzzy logic controller (FLC) according to required operation point of the system. Thus, adaptive nature of the FLC and robust structure of the PI controller are synthesised. Eventually, an adaptive PI controller which can adopt changes because of different operation conditions, grid disturbances and natural effects with fast transient response is obtained. Simulation studies are validated with experimental results. Both simulation and experimental results show that proposed system has fast dynamic response and tracks reference current with a low overshot and short settling time. In addition, the waveform of the inverter output current is sinusoidal and also the current is in same phase and frequency with the line voltage. Furthermore, the total harmonic distortion level of the inverter current meets the international standards. In addition, the proposed inverter system is compared with conventional PI controlled grid interactive inverter with various proportional and integral gains.